Lending structure and bank risk exposures: the case of Islamic and conventional banks in Malaysia - Aisyah binti Abdul Rahman (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2009)
This research investigates the impact of lending structure and the other bank specific variables on the six types of risk exposure: insolvency risk, market risk, interest rate risk, exchange rate risk, total risk, and unsystematic risk. The insolvency risk exposure is based on the Zrisk index developed by Hannan and Hanweck (1988) while the other five risk exposures are estimated based on the three-factor Capital Asset Pricing Model (CAPM). For each risk exposure, four lending structure measures are analysed namely, the real estate lending, the specialization index, the short run lending stability, and the medium term lending stability. Further, a comparative analysis of the risk behaviour between the Islamic and conventional banks is made. In addition, the effect of bank consolidation program and financial crisis period is incorporated. Using Generalised Least Square (GLS) panel regression techniques, three different data sets are analysed individually for the period of 1994 to 2006. Out of the three GLS models (the none effect, the fixed effect and random effect), the best model is selected based on the Likelihood Ratio (LR) and Hausman test. In general, the findings in this study show that real estate lending is positively related to the insolvency risk exposure of the conventional banks, but negatively related to the Islamic banks. Meanwhile, the lending structure variables to some extent affect the market, interest rate and unsystematic risk exposures. Also, this study finds that each risk exposure has different determinants. Hence, the policy makers, practitioners, and investors should react accordingly in the decision making process.